KLAUZULA EX BONA FIDE W FORMUŁCE KOMODATU - Zabłocki, Jan (Zeszyty Prawnicze, 2017)
The Clause ex bona fide of the formula commodati Summary From the passages on a competition of complaints one may conclude that before introduction of actio commodati one secured a protection of facts of a case, acknowledged later as a commodatum by using actio furti, condictio ex causa furtiva or actio legis Aquiliae. Commodatum gained a separate legal protection only as a result of pretor’s activities. Pretor introduced to his edict legal form u la e serving to pursue claims arising from com m odatum (D. 13,6,1 pr. - Ulp. 28 ad ed.). In Gaius’ opinion (G. 4,47) they are similar to deposit form ulae whereby he seems to suggest that a fo rm u la in ius com m odati had an ex bona fid e clause. On the other hand, placing com m odatum in pretor’s edict in the title de rebus creditis (D. 12,1,1,1 - Ulp. 26 ad ed.), and also a lack of certainty - due to a distortion of a text - whether Gaius (G. 4,62) in his enumeration of actiones bonae fidei took into account also commodatum may raise a doubt whether actio com m odati actually had this clause. However there is an indirect evidence attesting to the fact that com m odatum contained a good faith clause namely the possibility of compensation (G. 4,61; D. 13,6,18,4 - Gaius 9 a d ed. p ro v ) and release from an obligation in case of joint and several debt from commodatum not in a moment of litis contestatio but not until a fulfilment of an obligation (D. 13,6,5,15 - Ulp. 28 a d ed.).